A Predictive Instrument for Sensitive and Expedited Measurement of Ultra-Barrier Permeation. (October 2021) - Wanyan, Jianfeng; Cao, Kun; Chen, Zhiping; Li, Yun; Liu, Chenxi; Wu, Runqing; Zhang, Xiao-Dong; Chen, Rong
Abstract: The reliable operation of flexible display devices poses a significant engineering challenge regarding the metrology of high barriers against water vapor. No reliable results have been reported in the range of 10 –6 g∙(m 2 ∙d) −1, and there is no standard ultra-barrier for calibration. To detect trace amount of water vapor permeation through an ultra-barrier with extremely high sensitivity and a greatly reduced test period, a predictive instrument was developed by integrating permeation models into high-sensitivity mass spectrometry measurement based on dynamic accumulation, detection, and evacuation of the permeant. Detection reliability was ensured by means of calibration using a standard polymer sample. After calibration, the lower detection limit for water vapor permeation is in the range of 10 –7 g∙(m 2 ∙d) −1, which satisfies the ultra-barrier requirement. Predictive permeation models were developed and evaluated using experimental data so that the steady-state permeation rate can be forecasted from non-steady-state results, thus enabling effective measurement of ultra-barrier permeation within a significantly shorter test period.